2019
DOI: 10.1111/ijfs.14318
|View full text |Cite
|
Sign up to set email alerts
|

Improved solubility of banana starch by dielectric barrier discharge plasma treatment

Abstract: SummaryA novel technology for banana starch modification has been developed using dielectric barrier discharge (DBD) plasma, and the effect of DBD plasma treatment on the solubility and pasting behaviours of banana starch were evaluated. The solubility of treated starch significantly increased from 1.35 to 15.05 g 100 g−1 at 55 °C as the treatment intensity increased. Rapid viscosity analyser examination showed a dramatic change in the pasting behaviours of modified starch, and the peak viscosity decreased fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
20
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 27 publications
8
20
0
3
Order By: Relevance
“…The formation of these species makes PAW useful in microbial decontamination ( Lin et al, 2020 ), enhancing plant growth and seed germination ( Judée et al, 2018 ) as well as starch modification (Y. Yan et al, 2020 ). More details on the mechanism and potential applications of PAW in food are highlighted in Thirumdas et al (2018) .…”
Section: Plasma-activated Water (Paw)mentioning
confidence: 99%
See 1 more Smart Citation
“…The formation of these species makes PAW useful in microbial decontamination ( Lin et al, 2020 ), enhancing plant growth and seed germination ( Judée et al, 2018 ) as well as starch modification (Y. Yan et al, 2020 ). More details on the mechanism and potential applications of PAW in food are highlighted in Thirumdas et al (2018) .…”
Section: Plasma-activated Water (Paw)mentioning
confidence: 99%
“…Cold plasma and PAW are utilized in food decontamination, shelf-life extension, and seed germination ( Sarangapani et al, 2017 ; Thirumdas et al, 2018 ). Cold plasma is also explored in the modification of food components, including starches, proteins ( Mahdavian Mehr and Koocheki, 2020 ; S. Yan et al, 2020 ; Y. Yan et al, 2019 ; Bu et al, 2022 ), food fortification ( Aditya et al, 2020 ), and in treatment of films ( Song et al, 2019 ).…”
Section: Recent Applications Of Cold Plasma In Food Processingmentioning
confidence: 99%
“…g), due to depolymerization of amylopectin side chains. Therefore, determining the amylose content in plasma-treated starches may give a false result of increased amylose in the starch granule.Starch depolymerization can increase the binding capacity with polyphenols by approximately 10-fold, as observed byGao et al (2021), or the water solubility, as reported byYan et al (2020) in banana starch.Sifuentes-Nieves et al (2021) evaluated corn starches with different amylose contents in the presence of HMDSO (Hexamethyl di-siloxane) subjected to NTP with different gases (atmospheric air, O2, N, Ar) and reactors (RF and DBD). The authors reported that the results favored the ordering and stability of the amylose molecule; thus, it can be used in the food industry and/or other fields such as semiconductors.…”
mentioning
confidence: 56%
“…They can be modified by various chemical, physical, enzymatic, and genetic methods, emphasizing physical methods for not generating effluents (Maniglia et al, 2021). Alternative starch sources and physical modification processes have been studied to extend the applicability of this carbohydrate, including the use of NTP in the unconventional buckwheat starch (Gao et al, 2021) and banana (Yan et al, 2020).…”
Section: Starchmentioning
confidence: 99%
See 1 more Smart Citation